AKAL DAN WAHYU - Riska Amaliah Amaliah; Andi Resky Yuliana Sari; Abbas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reason and revelation are two main sources of knowledge in Islam that play an important role in shaping religious understanding, scientific development, and Islamic civilization. Revelation is viewed as an absolute truth originating from Allah SWT, while reason is a rational potential granted to humans to understand, interpret, and implement the values of revelation in real life. This study aims to analyze the relationship between reason and revelation in the Islamic perspective and examine their relevance to the development of knowledge and civilization. This research employed a qualitative approach using a literature review method by analyzing books and scientific journal articles relevant to the topic. The results of the study indicate that reason and revelation are not contradictory but complementary. Revelation provides moral and spiritual guidance, while reason functions as an analytical tool to contextualize Islamic teachings so that they remain relevant to the dynamics of modern life. The integration of reason and revelation is essential in developing ethical knowledge grounded in divine values. Keywords: reason, revelation, Islamic perspective